Analisis Semiotika Pada Puisi “Akulah Si Telaga” Karya Sapardi Djoko Damono - Adi Muhamad Fadilah; Romdin Romeo Hakim (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
Poetry is an expression of the soul through aesthetic words. In a poem there is always something contained in several markers, both in the form of meanings that need to be translated by the readers themselves and linguistic markers that do not require reinterpretation. The field of study that studies and examines signifiers, symbols and signs in a field of study is called semiotics. Semiotics is a scientific study that studies the signs that exist in a literary work, these signs represent something else, not the real thing. Therefore, a semiotic approach in poetry will clarify the meaning that has been a sign in the expression of a poet. The goal that researchers want to get from this paper is to be able to analyze and also know the meaning contained in the poem "Akulah Si Telaga". The method chosen for research on the poem "Akulah Si Telaga" uses a qualitative research method which examines writing based on the content of the literary works of poetry studied. In addition, this poem is analyzed using a semiotic approach whose discussion is more focused on the theory of sassurue about the development of linguistics. The results of the analysis of the poem "Akulah Si Telaga" using this semiotic approach produce two aspects, namely; icon, and index.